Qualitative Olfactory Disorders: Patient Experiences and Self-Management. (September 2021) - Philpott, Carl; Dixon, Joanne; Boak, Duncan
Background: Qualitative olfactory disorders in the form of parosmia and phantosmia are very subjective and cannot be measured at present. They pose an unpleasant experience for patients and a therapeutic challenge for clinicians. Objective: This study aimed to characterise the specific experiences of patients affected by the qualitative symptoms of parosmia and phantosmia including both triggers for symptoms and self-help measures they have tried. Methods: A cross-sectional survey questionnaire was developed with the input of patient experts within the charity Fifth Sense. The survey was then open online for 3 months to charity members complaining of qualitative symptoms. The survey captured the frequency and impact of symptoms and self-management undertaken. Reflective feedback was also captured from a patient workshop. Results: There were 100 participants; 61% female, age range 13-88. Common self-reported aetiology included sinonasal disease (17%), idiopathic (33%) and post-viral olfactory loss (26%) and post-traumatic olfactory loss (23%). Parosmia was reported as a daily symptom in 67% compared to 31% for phantosmia; 36% complained of suffering with both symptoms. Only 4% of respondents reported having received any successful treatment for their qualitative symptoms and 58% reported having received no treatment whatsoever. Olfactory training was the most common self-management method reported. Conclusion: This study illustrates that qualitative disturbances remain problematic for those who experience them due to the duration of symptoms, the relative lack of experience or knowledge amongst medical professionals and the lack of therapeutic options. In future, consideration needs to be given to adaptation and coping strategies to help patients deal with these symptoms.